Multispecies Assessment of Factors Influencing Regional CO2 and CH4 Enhancements During the Winter 2017 ACT‐America Campaign. Issue 2 (22nd January 2020) - Baier, Bianca C.; Sweeney, Colm; Choi, Yonghoon; Davis, Kenneth J.; DiGangi, Joshua P.; Feng, Sha; Fried, Alan; Halliday, Hannah; Higgs, Jack; Lauvaux, Thomas; Miller, Benjamin R.; Montzka, Stephen A.; et al.
Abstract: Diagnosing carbon dioxide ( CO 2 ) and methane ( CH 4 ) fluxes at subcontinental scales is complicated by sparse observations, limited knowledge of prior fluxes and their uncertainties, and background and transport errors. Multispecies measurements in flasks sampled during the wintertime ACT‐America campaign were used for background characterization and source apportionment of regional anthropogenic CO 2 and CH 4 fluxes when ecosystem CO 2 exchange is likely to be least active. Continental background trace gas mole fractions for regional enhancements are defined using samples from the upper troposphere and assessed using model products. Trace gas enhancements taken from flask samples in the lower troposphere with background levels subtracted out are then interpreted to inform CO 2 and CH 4 enhancement variability in the eastern United States. Strong correlations between CO 2 and CH 4 enhancements in the Midwestern and Mid‐Atlantic United States indicated colocated anthropogenic sources. Oil and natural gas influence was also broadly observed throughout the entire observational domain. In the Midwestern United States, agricultural influence on CO 2 and CH 4 enhancement variability was evident during above‐average wintertime temperatures. Weaker correlations between CO 2 and anthropogenic tracer enhancements in the Southeastern United States indicated potentially nonnegligible wintertime ecosystem CO 2 exchange, with biogenic tracers indicating more active surface processing than other regions. These whole‐air flask samples illuminated significant regional CO 2 and CH 4 sources or sinks during Atmospheric Carbon and Transport‐America (ACT‐America) and can provide additional information for informing regional inverse modeling efforts. Key Points: Multispecies flask samples are used to characterize regional wintertime eastern U.S. CO2 and CH4 enhancement variability Mid‐Atlantic and Midwestern U.S. CO2 and CH4 enhancements are primarily anthropogenic Winter Southeastern U.S. CO2 and CH4 enhancements indicate influence from biogenic exchange and surface processing